Māori experiences of multiple forms of discrimination: findings from Te Kupenga 2013 - Cormack, Donna; Harris, Ricci; Stanley, James (Kōtuitui: New Zealand Journal of Social Sciences Online, 2020)
Comprehensive exploration of Māori experiences of discrimination in Aotearoa New Zealand remains limited, particularly in relation to exposure to multiple and interlocking forms of discrimination. This paper presents findings from a secondary analysis of Te Kupenga 2013, the first Māori Social Survey, examining patterning and prevalence of different forms of discrimination for Māori (n = 5,549). Māori report experiencing multiple forms of discrimination, both over their lifetimes and within the last year. Although racial discrimination was the most commonly reported form, Māori also experience discrimination on the basis of other grounds including age, gender, and income. Māori also report exposure to multiple forms of discrimination. Discrimination occurred in a range of settings, with schools and workplaces common sites. The findings support the lived reality of Māori that racial and other forms of discrimination are pervasive, and experienced in multiple domains across the life course, representing a persistent breach of rights. It is critical that other forms of discrimination are measured alongside racism in order to understand and address the realities of multiple discrimination for Māori in Aotearoa New Zealand.
Keywords: discrimination; racism; te kupenga; treaty obligations

The relationship between socially-assigned ethnicity, health and experience of racial discrimination for Māori: analysis of the 2006/07 New Zealand Health Survey - Harris, Ricci B.; Cormack, Donna M.; Stanley, James (BMC Public Health, 2013)
In New Zealand, there are significant and long-standing inequalities in a range of health outcomes, risk factors and healthcare measures between Māori (indigenous peoples) and Pākehā (European). This study expands our understanding of racism as a determinant of such inequalities to examine the concept of socially-assigned ethnicity (how an individual is classified by others ethnically/racially) and its relationship to health and racism for Māori. There is some evidence internationally that being socially-assigned as the dominant ethnic group (in this case European) offers health advantage.
Keywords: discrimination; ethnic identity; ethnicity; health; identity; inequity; racism; trauma